2018
DOI: 10.1111/ppa.12924
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variation of Pyrenophora teres f. teres isolates in Western Australia and emergence of a Cyp51A fungicide resistance mutation

Abstract: Genome‐wide, unlinked, simple sequence repeat markers were used to examine genetic variation and relationships within Pyrenophora teres f. teres, a common pathogen of barley, in Western Australia. Despite the region's geographic isolation, the isolates showed relatively high allelic variation compared to similar studies, averaging 7.11 alleles per locus. Principal component, Bayesian clustering and distance differentiation parameters provided evidence for both regional genotypic subdivision together with juxta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 45 publications
0
24
0
Order By: Relevance
“…Model-based genetic structuring analysis of 188 P. teres f. teres isolates indicated that the most likely number of clusters is two. This is the same number of K groups as identified by Ellwood et al (2019) using isolates from Western Australia only. An association between the clusters and some of the phenotypic assessments of the isolates was observed with most of the isolates virulent on Beecher, Maritime, and Prior clustering in one group and those showing greater infection rates on Herta and Skiff clustering in group 2.…”
Section: Discussionmentioning
confidence: 62%
“…Model-based genetic structuring analysis of 188 P. teres f. teres isolates indicated that the most likely number of clusters is two. This is the same number of K groups as identified by Ellwood et al (2019) using isolates from Western Australia only. An association between the clusters and some of the phenotypic assessments of the isolates was observed with most of the isolates virulent on Beecher, Maritime, and Prior clustering in one group and those showing greater infection rates on Herta and Skiff clustering in group 2.…”
Section: Discussionmentioning
confidence: 62%
“…This represents a contrast with the situation reported in Ptt where all mutant strains had an identical Cyp51A sequence and the F489L (F495L) substitution was always associated with the same single nucleotide polymorphism, c1467a for codon TTA (Mair, Deng, et al 2016). A subsequent study using microsatellite markers suggested that this polymorphism most likely arose in Ptt from a single mutational event that subsequently recombined into different genetic backgrounds and spread through the pathogen population (Ellwood et al 2019). By comparison, in this study the mutation F489L (F495L) was caused by three different single nucleotide polymorphisms and each of these three SNPs were found in a distinct Cyp51A haplotype.…”
Section: Discussionmentioning
confidence: 63%
“…As Ptt is dispersed on infected seed, phylogenetic similarities may also be related to cultivation of historic cultivars, for example the American cultivar Beecher in Western Australia. Alternatively, as the genotypes in Australia appear to represent a subset of USA and European diversity, and with recent population studies confirming two groups occur in Australia [33,35], the genotypes present in Australia may represent chance incursions.…”
Section: Pyrenophora Whole Genome Comparative Analysismentioning
confidence: 99%